Management of Airways through Rapid Tracheostomy in a Severely Burnt Patient Attended to via Helicopter. (2nd July 2021) - Filippelli, Orazio Stefano Giovanni; Giglio, Anna Maria; Tiburzi, Simona Paola; Archinà, Maria Teresa; Barozzi, Ercole; Maglio, Pietro; Candido, Stefano; Viotti, Roberta; Riccelli, Umberto; Pezzi, Mario; Romano, Carmelo; Scozzafava, Anna Maria; et al.
Abstract : In Catanzaro, Italy, an adult male with severe burns all over his body and in a state of coma was promptly rescued by the medical team at the air ambulance service (HEMS), who provided airway safety through laryngeal mask placement (LMA). The patient was subsequently transferred to the nearest Hub center, where an emergency tracheostomy was performed to ensure better airway management during the flight to the nearest available major burn center. This is the first documented case at regional level of a patient undergoing rapid tracheostomy through an imminent transfer with air ambulance.